Fatty acid composition, anti-inflammatory and analgesic activities of Hibiscus sabdariffa Linn. seeds - Ali, Sumaia Awad Elkariem; Mohamed, Abdelwahab Hassan; Mohammed, Galal Eldin Elazari (Journal of Advanced Veterinary and Animal Research, 2014)
Hibiscus (H.) sabdariffa (commonly known as Karkadeh in Arabic) is widely used in various pharmacological applications in Sudan. The present study was carried out to investigate the anti-inflammatory and analgesic activities of H. sabdariffa seed extracts using rat models. In acute anti-inflammatory models, oral administration of petroleum ether extract of H. sabdariffa seeds inhibited the hind paw edema (p<0.01) which was induced by carrageenan. The petroleum ether extract exhibited significant (p<0.01) inhibition of vascular permeability in rats induced by intraperitoneal injection of acetic acid (0.6%). In cotton pellet granuloma method, the petroleum ether extract of H. sabdariffa seed showed significant inhibition of granuloma. The extract reduced (p<0.001) abdominal constrictions which was induced by injection of acetic acid (0.7%). Analysis of seed oil of H. sabdariffa using Gas Chromatography revealed the presence of three fatty acids; these were linolelaidic acid, arachidic acid, and palmitic acid. In conclusion, H. sabdariffa seeds possess anti-inflammatory and analgesic activities in rat model. DOI: http://dx.doi.org/10.5455/javar.2014.a13 J. Adv. Vet. Anim. Res., 1(2): 50-57, June 2014